Effect of Strenuous Exercise on Fibrinogen and Fibrinolysis in Healthy Elderly Men and Women - Schuit, Albertine J; Schouten, Evert G; Kluft, Cornelis; de Maat, Moniek; Menheere, Paul P C A; Kok, Frans J (Thrombosis and Haemostasis, 1997)
The elevated incidence of thrombotic disease in elderly people may be associated with an increase in PAI-1 and fibrinogen with ageing. Cross-sectional studies report an inverse relation of PAI-1 and fibrinogen with physical activity, but training studies show inconsistent results. In a controlled intervention study among elderly subjects (aged 60-80 years) we observed a moderate decrease in PAI-1 antigen (4%, -2.1 ± 2.4 ng/ml), a significant increase in t-PA activity (11%, 0.07 ± 0.04 IU/ml) and an unexpected significant increase in fibrinogen (6%, 0.18 ± 0.07 g/1) in subjects following a 6-month intensive training program as compared to controls. Reduction in PAI-1 antigen was significantly associated with a decrease in triglycerides (β = 10.3 ng/ml per 1 mM, p <0.01) and insulin (β = 2.37 ng/ml per 1 mU/1, p = 0.07). Increase in fibrinogen coincided with a rise in C-reactive protein (p <0.001). These data suggest that regular intensive activity may increase fibrinolytic activity in a moderate way, but also may cause chronically elevated plasma levels of acute phase proteins in elderly persons.